2013
DOI: 10.1002/chin.201336202
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Recent Advancements of Copper as an Inexpensive and Mild Catalyst in Heterocyclic Synthesis

Abstract: Review: 152 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Therefore, such processes are ultimately useful in saving energy and minimizing the waste formation . Transition metal catalysis has been proven to be an efficient tool for the development of new synthetic methods, especially in the creation of new C–C and C–X heteroatom bonds with increasing molecular complexity . In continuation of our ongoing research interests in domino processes using transition metal-catalysis, we have reported an efficient [Cu]-catalyzed domino one-pot method for the synthesis of isobenzofuran-1­(3 H )-ones using nontoxic K 4 [Fe­(CN) 6 ] as the source of CO, under environmentally benign conditions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such processes are ultimately useful in saving energy and minimizing the waste formation . Transition metal catalysis has been proven to be an efficient tool for the development of new synthetic methods, especially in the creation of new C–C and C–X heteroatom bonds with increasing molecular complexity . In continuation of our ongoing research interests in domino processes using transition metal-catalysis, we have reported an efficient [Cu]-catalyzed domino one-pot method for the synthesis of isobenzofuran-1­(3 H )-ones using nontoxic K 4 [Fe­(CN) 6 ] as the source of CO, under environmentally benign conditions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, transition-metal-catalyzed domino reactions have become a research hotspot during the past decades for their ability to shorten reaction procedures, reduce waste, and use milder conditions . As a member of the transition-metal family, copper not only displays great catalytic potential in many transformations but also has many advantages such as low toxicity, low cost, and easy handling . Thus, copper-catalyzed domino reaction toward cyclic compounds is receiving more attention these days .…”
mentioning
confidence: 99%